Using GIS to analyse the impact of a new motorway in industrial location - Ramos, Rui A. R. (1996)
In recent years, the eccessibility patters in Portugal are being changed due to motorways. This is the case of the Northwest port of Portugal, where the new motorway A3, between Oporto and Braga, has been introduced in 1991. Because this new infrastructure has increased the accessibility to the sea port and airport of Oporto and to the main transport axes of the country, it seems to be time to a first approech to the stydy of its impact in the process of industrial location. In this paper a GIS-based model is developed in order to evaluate the impact of a change of accessibility in industrial location. Factors such as the proximity to the population, motorway nodes and urban centres are evaluated and time-spatially referenced in order to detect trends. An application of the model is presented.